Speech Acts in the Bastem Traditional Wedding Ceremony (Rampanan Kapa'): An Ethnopragmatic Study in South Sulawesi - Nurhayati, A.; Sari, Harmita; Aliah, Husnani; Aco, Dedi (Universitas Muhammadiyah Malang, 2026)
This research is motivated by the importance of understanding language as a medium for shaping social values ​​and cultural identity in the Bastem community, South Sulawesi. The Rampanan Kapa' traditional wedding ceremony is not only a ritual for uniting two families, but also an arena for symbolic communication imbued with values ​​of politeness, spirituality, and social solidarity. The main problem of this research is the form, meaning, and function of the speech acts used in each stage of the ceremony, and how these utterances reflect local cultural values ​​and the politeness system of the Bastem community. This research uses a qualitative descriptive method with an ethnopragmatic approach, which connects the analysis of linguistic forms with the sociocultural context. Data were obtained through direct observation, in-depth interviews, documentation, and recording of speech acts used during the traditional procession. The results show four main types of speech acts—representative, expressive, directive, and declarative—that function to regulate social relations, affirm customary norms, and mark the social legitimacy of the marriage. Customary speech also serves as a means of transmitting moral values ​​such as deliberation, politeness, and respect for ancestors. The research conclusion confirms that the Bastem traditional language is not just a means of communication, but rather a social and spiritual mechanism that connects humans with their communities and cultures, as well as being a means of preserving the collective identity of local communities.